2015
DOI: 10.2147/dddt.s78658
|View full text |Cite
|
Sign up to set email alerts
|

Comparative fasting bioavailability of two clopidogrel formulations in healthy Mediterranean volunteers: an in vitro–in vivo correlation

Abstract: ObjectiveThe aim of this study was to evaluate the bioequivalence of two drug products, generic clopidogrel bisulfate 75 mg film-coated tablets versus the reference Plavix® clopidogrel bisulfate 75 mg film-coated tablets.MethodsBioequivalence of tablets was tested by comparisons against the reference brand product in accordance with the requirements of the Declaration of Helsinki, the current Good Clinical Practice Guidelines, and the International Conference on Harmonization.ResultsThe relationship between co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
2
4
0
Order By: Relevance
“…Similar results were also obtained by Cooper-Dehoff and Elliott who compared patent and generic drugs of some blood pressure lowering agents that included beta-blockers, diuretics, and calcium antagonists [10]. Some other studies on clopidogrel and candesartan tablets also reported bioequivalence between their patent and generic products [11,12].…”
Section: Introductionsupporting
confidence: 77%
“…Similar results were also obtained by Cooper-Dehoff and Elliott who compared patent and generic drugs of some blood pressure lowering agents that included beta-blockers, diuretics, and calcium antagonists [10]. Some other studies on clopidogrel and candesartan tablets also reported bioequivalence between their patent and generic products [11,12].…”
Section: Introductionsupporting
confidence: 77%
“…Similar results were also obtained by Cooper-Dehoff and Elliott who compared patent and generic drugs of some blood pressure lowering agents that included beta-blockers, diuretics, and calcium antagonists [10]. Some other studies on clopidogrel and candesartan tablets also reported bioequivalence between their patent and generic products [11,12]. Methylprednisolone (MP) is a corticosteroid anti-inflammatory drug classified to glucocorticoid.…”
Section: Introductionsupporting
confidence: 64%
“…Clopidogrel, prasugrel and ticagrelor are all adenosine diphosphate (ADP) antagonists, a class of therapeutic agents that bind selectively to the P2Y 12 receptor to inhibit platelet function (see Figure 1 and Table 1). 23 The thienopyridine, ticlopidine was the first drug in this class but is seldom prescribed now, following reports of serious adverse reactions, in particular neutropaenia 24 and thrombotic thrombocytopaenic purpura. 25…”
Section: Adenosine Diphosphate Receptor Antagonists In Acute Coronarymentioning
confidence: 99%
“…It is administered orally and up to 85 % of the absorbed drug undergoes hepatic metabolism by carboxylesterases to form an inactive carboxylic acid derivative, clopidogrelic acid, whilst the remaining 15 % is metabolised into the active thiol product by cytochrome P450 isoenzymes. 23,26 Although clopidogrel has a relatively short half-life of 6 hours, 27 28 Variable responses to clopidogrel may additionally result from mutations in the ABCB1 gene that encodes the P-glycoprotein involved in clopidogrel absorption. 28 The standard dosing regime is a 300 mg loading dose and 75 mg daily maintenance dose.…”
Section: Clopidogrelmentioning
confidence: 99%